A man of honor [large type] - Bradford, Barbara Taylor, 1933- (Bradford, Barbara Taylor, 1933- Emma Harte saga, 2022)
"Opening five years before the start of A Woman of Substance, A Man of Honor begins with 13-year-old Blackie O'Neill facing an uncertain future in rural County Kerry. Orphaned and alone, he has just buried his sister, Bronagh, and must leave his home to set sail for England, in search of a better life with his mother's brother in Leeds. There, he learns his trade as a navvy, amid the grand buildings and engineering triumphs of one of England's most prosperous cities, and starts to dream of greater things ... And then, high on the Yorkshire moors, in the mists of a winter morning he meets a kitchen maid called Emma Harte."--